(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The article presents a comparative analysis of two modernist models of residential environment organization that emerged in the first third of the 20th century: based on related planning units – the Western “neighbourhood unit” and the Soviet microdistrict. Both emerged as responses to the universal challenges of industrial urbanization – the housing crisis, accelerated urban growth, transport conflicts and the need to ensure everyday functions within pedestrian accessibility – but developed in fundamentally different political and institutional systems. The paper examines whether these models were parallel responses to common challenges, whether there was a direct or indirect mutual influence between them, and determines the universality and contextual conditionality of their implementation. An attempt is made to identify similarities and differences in the processes of emergence and transformation of the neighbourhood and microdistrict, as well as possible relationships between them. The evolution of the "neighbourhood unit" in the United States is examined, from the early works of W. E. Drummond to its normative formulation by C. A. Perry in 1929 in the concept of the Regional Plan of New York and its environs; the role of British experience in the formation of socially oriented planning, in particular the activities of T. Adams and the Russell Sage Foundation, is outlined. A system of key planning principles of the "neighbourhood unit" is identified (bordering highways, eliminating transit, centricity of schools and public functions, a system of open spaces). In parallel, the genesis of the Soviet microdistrict is analysed: the developments of the “Dipromisto” institute in the 1930s under the leadership of O. Eingorn, the change in approaches in the post-war period, the normative restoration of the microdistrict principle in the second half of the 1950s and its large-scale implementation until the beginning of the 1990s, including subsequent modifications (the “focusing” method of L. Tulpa). It is shown that the similarity of the initial problems caused the similarity of a number of planning principles, however, different implementation mechanisms – experimental-developmental in the West and centralized-normative in the USSR – determined different development trajectories and practical effects of these models.